Effect of push-pull factors on brain drain intention among doctors in Iraq - Oraibi, Bha Aldan Mundher (2021)
While one of the more devastating effects of organizational deterioration and crises is brain drain (BD), it has received only a cursory mention in organizational research. BD antecedents, especially from an organizational perspective, have remained largely unexplored. To address this void, the present study proposes a conceptual framework for BD in organizations. A model comprising the antecedents of BD and the BD intention, and an analysis of BD leavers' behavioral characteristics, is introduced and tested. This study, which draws from 450 doctors working in the public hospitals in Iraq, showed that the BD intention of the remaining doctors in Iraq is derived from autocratic management style, alternative job opportunities, upward comparison, opportunities for career advancement and success, attitude towards BD, descriptive norm, exposure to violence, intention to work abroad, and occupational distress. However, the perceived workload, injunctive norm, subjective norm, and perceived employability did not directly influence their BD intention. This study also found a significant mediating effect of occupational distress and attitude towards BD between the studied push-pull factors, social-behavioral processes of BD leavers, and their consequences. This study concludes by highlighting the theoretical implications of examining the effect of organizational/occupational level factors and leavers' behavioral characteristics to explain the BD from an organizational perspective. Several important implications for practice are also discussed.